2022
DOI: 10.1097/md.0000000000029819
|View full text |Cite
|
Sign up to set email alerts
|

Effect of binaural beat in the inaudible band on EEG (STROBE)

Abstract: This study aimed to determine the effects of the binaural beat (BB) on brainwave induction using an inaudible baseline frequency outside the audible frequency range. Experiments were conducted on 18 subjects (11 males [mean age: 25.7 ± 1.6 years] and 7 females [mean age: 24.0 ± 0.6 years]). A BB stimulation of 10 Hz was exerted by presenting frequencies of 18,000 Hz and 18,010 Hz to the left and right ears, respectively. A power spectrum analysis was performed to estimate the mean of the absolute power of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Our research team addressed this issue by eliminating the in uence of audible sounds in prior studies and observed the brainwave entrainment effects of BB. Speci cally, we validated the ability of inaudible BB with a base frequency of 18000 Hz and a differential frequency of 10 Hz to induce alpha waves [12].…”
Section: Introductionmentioning
confidence: 87%
“…Our research team addressed this issue by eliminating the in uence of audible sounds in prior studies and observed the brainwave entrainment effects of BB. Speci cally, we validated the ability of inaudible BB with a base frequency of 18000 Hz and a differential frequency of 10 Hz to induce alpha waves [12].…”
Section: Introductionmentioning
confidence: 87%
“…Additional studies are required to reliably verify the pure effects of binaural beats stimulation by removing all sound factors that may be perceived by the subjects. Previous work done by our group found evidence of increased alpha power using an inaudible reference frequency of 18 000 Hz and a difference frequency of 10 Hz [18].…”
Section: Introductionmentioning
confidence: 99%